Modeling and calculation of the technological process of testing piston hydraulic cylinders with energy recovery - Rybak Alexander; Zenin Alexander; Pelipenko Alexey (E3S Web of Conferences, 2023)
One of the most important problems of modern mechanical engineering is the energy efficiency of technological equipment and manufactured products. A separate issue in this series is the technology and means of testing finished product samples, including hydraulic machines. In this article, an original scheme of a test bench for piston hydraulic cylinders and a method of mathematical modeling of the process of its functioning, based on the application of the theory of volumetric rigidity of hydraulic systems, is proposed, which makes it possible to describe with high accuracy and reliability the processes occurring in the test system during its operation. The test efficiency coefficient is proposed, which makes it possible to evaluate and compare various test processes by the criterion of their energy efficiency. An example of a preliminary calculation of the functioning of the proposed stand is given.